'The medicine is not for sale': Practices of traditional healers in snakebite envenoming in Ghana. - Jonathan Steinhorst; Leslie Mawuli Aglanu; Sofanne J Ravensbergen; Chrisantus Danaah Dari; Kabiru Mohammed Abass; Samuel Osei Mireku; Joseph Ken Adu Poku; Yeetey A K Enuameh; Jörg Blessmann; Robert A Harrison; John H Amuasi; Ymkje Stienstra (Public Library of Science (PLoS), 2021)
Background Snakebite envenoming is a medical emergency which is common in many tropical lower- and middle-income countries. Traditional healers are frequently consulted as primary care-givers for snakebite victims in distress. Traditional healers therefore present a valuable source of information about how snakebite is perceived and handled at the community level, an understanding of which is critical to improve and extend snakebite-related healthcare. Method The study was approached from the interpretive paradigm with phenomenology as a methodology. Semi-structured interviews were conducted with 19 traditional healers who treat snakebite patients in two rural settings in Ghana. From the Ashanti and Upper West regions respectively, 11 and 8 healers were purposively sampled. Interview data was coded, collated and analysed thematically using ATLAS.ti 8 software. Demographic statistics were analysed using IBM SPSS Statistics version 26. Findings Snakebite was reportedly a frequent occurrence, perceived as dangerous and often deadly by healers. Healers felt optimistic in establishing a diagnosis of snakebite using a multitude of methods, ranging from herbal applications to spiritual consultations. They were equally confident about their therapies; encompassing the administration of plant and animal-based concoctions and manipulations of bite wounds. Traditional healers were consulted for both physical and spiritual manifestations of snakebite or after insufficient pain control and lack of antivenom at hospitals; referrals by healers to hospitals were primarily done to receive antivenom and care for wound complications. Most healers welcomed opportunities to engage more productively with hospitals and clinical staff. Conclusions The fact that traditional healers did sometimes refer victims to hospitals indicates that improvement of antivenom stocks, pain management and wound care can potentially improve health seeking at hospitals. Our results emphasize the need to explore future avenues for communication and collaboration with traditional healers to improve health seeking behaviour and the delivery of much-needed healthcare to snakebite victims.